The Impact of Open Innovation (OI) on Competitive Advantage (CA) in Presence of Knowledge Coupling (KC): An Empirical Study on Small and Medium Enterprises (SMEs), District of Gujranwala, Pakistan - Usman, Muhammad; Khan, Muhammad Imran; Khattak, Asmat Nawaz (Pakistan Journal of Humanities and Social Sciences, 2024)
SMEs play a major role in domestic growth and essential to the economy of every country. The study investigated the impact of "open innovation" on "competitive advantage" in the presence of "knowledge coupling" in SMEs in Pakistan. The study used a quantitative research design and tested the hypotheses. A sample of 290 employees from SMEs in District Gujranwala, Pakistan, was selected using a simple random probability technique. The research study used SPSS software to compute regression analysis, mediation analysis, and correlation analysis. The study's conclusions show that "open innovation" is essential to "competitive advantage." For Pakistani SMEs, concentrating on "open innovation" may provide a "competitive advantage." The study went on to conclude that "open innovation" and "knowledge coupling" are crucial for gaining a "competitive advantage" because they allow companies to leverage outside ideas and experience, which accelerates innovation and reduces research and development (R&D) costs. The effectiveness of "open innovation" in boosting a company's competitiveness is determined by its capacity to successfully integrate internal and external knowledge.